Weak mineralization despite strong processing of dissolved organic matter in Eastern Arctic tundra ponds. Issue Volume 66:Issue S1(2021) Supplement (28th October 2020) - Laurion, Isabelle; Massicotte, Philippe; Mazoyer, Flora; Negandhi, Karita; Mladenov, Natalie
Abstract: Permafrost thawing mobilizes large quantities of organic carbon that was sequestered in Arctic regions over the last glacial cycle. Processes involved in the oxidation of this carbon need to be further assessed to estimate the fraction to be released into the atmosphere. Shallow tundra ponds are sites of active carbon turnover on the landscape and significant sources of greenhouse gases. Dissolved organic matter (DOM) leached from thawing peat into these ponds is exposed to sunlight, with the potential to accelerate its mineralization directly into CO2 or through the production of more labile molecules. We tested the catalytic effect of sunlight on DOM mineralization in tundra ponds formed on organic‐rich polygonal landscapes originating from syngenetic permafrost, including a pond exposed to active permafrost erosion. Microbial decay rates, measured as the loss of chromophoric DOM, were similar to photodecay rates (1%–3% d −1 ). Groups of fluorescing molecules were formed through microbial transformation or lost through photolysis at differing rates among studied ponds, with the erosive trough pond presenting a unique response suggesting the involvement of soil microbes. Despite the stimulation of microbial growth under sunlight and the dynamic response of DOM optical properties, the loss of dissolved organic carbon was not significant under any treatment. This suggests that microbial and photochemical mineralization of DOM was slow and potentially substrate‐limited during the dry period when ponds were sampled. The static nature of tundra ponds, with their long water retention time, may thus constrain hot moments when water moves and transports carbon on the landscape.